1981
DOI: 10.1002/clc.4960040408
|View full text |Cite
|
Sign up to set email alerts
|

Prinzmetal's variant angina induced only by alcohol ingestion

Abstract: JapanSummary: Prinzmetal's variant angina occurred in a 52-year-old man 10-1 1 h after the ingestion of alcohol, when blood levels of alcohol decreased almost to the zero level. Coronary arteriograms revealed significant narrowing in the left circumflex artery and the left anterior descending artery and minimal wall irregularity in the right coronary artery; however, both exercise and pharmacologic stress tests were negative. A withdrawal from an acute exposure to alcohol was discussed as a possible causative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In 12 patients with stable angina and angiographically defined coronary lesions who were exercised until angina developed after 0, 2, or 5 oz ethanol, there was a significant decrease in exercise duration after There have been multiple reports of ethanolinduced Prinzmetal's variant angina occurring several hours after oral ingestion. [16][17][18][19] In some of these patients, ethanol was the only stimulus that could induce angina, and angina was reproducible with rechallenge in others. Ethanol-induced angina occasionally occurred when ethanol levels were near zero, leading investigators to suspect a metabolite of ethanol or delayed release of a mediator rather than ethanol itself as the cause of symptoms.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…In 12 patients with stable angina and angiographically defined coronary lesions who were exercised until angina developed after 0, 2, or 5 oz ethanol, there was a significant decrease in exercise duration after There have been multiple reports of ethanolinduced Prinzmetal's variant angina occurring several hours after oral ingestion. [16][17][18][19] In some of these patients, ethanol was the only stimulus that could induce angina, and angina was reproducible with rechallenge in others. Ethanol-induced angina occasionally occurred when ethanol levels were near zero, leading investigators to suspect a metabolite of ethanol or delayed release of a mediator rather than ethanol itself as the cause of symptoms.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
“…15 Despite findings that suggest there may be a protective level of alcohol consumption between the extremes of abstention and drinking more than 3-4 drinks each day, there is evidence that ethanol use can provoke angina in patients with preexisting coronary artery disease. [16][17][18][19] Several studies of patients undergoing coronary angiography, primarily for symptoms of unstable angina and recent myocardial infarction, have demonstrated a lesser degree of atherosclerotic narrowing in heavy drinkers compared with light drinkers.20-22 This has been interpreted as evidence for a protective effect of ethanol on the coronary arteries. However, because the severity of symptoms leading to angiography in both groups was similar, these data could alternatively be interpreted to show that ethanol causes an earlier presentation of coronary artery disease because of some destabilizing or exacerbating effect.…”
Section: Ethanol Causes Epicardial Coronary Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…Since then several case reports have appeared [2,3]. In 1984 Takizawa et al [5] concluded in a more extensive study that alcohol-induced coro nary spasm occurs in quite a number of patients with Prinzmetal's angina.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of factors are known to be able to induce these attacks. Among others a rela tion between alcohol ingestion and coronary spasm has been established by several au thors [1][2][3][4][5], In these studies anginal attacks closely followed alcohol ingestion 1-12 h be fore. On the contrary the present report de scribes a patient in whom severe coronary spasm occurred 1-7 days after stopping longlasting excessive alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%